The African background of the prosperity gospel - Adamo, David T. (Theologia Viatorum, 2021)
Prosperity gospel refers to the genre of preaching that emphasises positive confession, divine physical healing, divine material success as necessary gifts, and blessing from God. In other words, it is the spiritualisation of materiality and celebration of the abundance, which comes from God as a result of divine promise from him. The prosperity gospel is a form of Pentecostalism. There are three ways in which the background of prosperity gospel can be traced to Africa: (1) African Traditional religious heritage; (2) African social–cultural heritage; and (3) historical heritage. This article seeks to examine these three ways in which the background of prosperity gospel can be traced to Africa. This is supported by the fact that the black culture has not been lost in the lives of the slaves even when languages, family bondages, ethnic belongings were unscrupulously destroyed, and Seymour, an African American, is the father of Pentecostalism, from which prosperity gospel was born.
free